Optimization of Biofertilizer Application on Sweet Corn Growth and Yield in Organic Farming Environment - Rochman, Fajar; Maharani, Juwita Suri; Yuriansyah (Politeknik Pertanian Negeri Samarinda, 2024)
This study looks at how to use biofertilizers to help sweet corn grow and yield well in an organic farming environment. The biofertilizers used were Trichoderma sp. fungus, Paenibacillus polymyxa bacteria, and a combination of the two with manure. The research was arranged in a Randomized Group Design (RAK) with four treatments and five replications. The treatments were control, manure and Trichoderma sp., Trichoderma sp. and P. polymyxa, and P. polymyxa alone. Parameters observed included plant height, number of leaves, stem diameter, cob length, cob diameter, cob weight, and sweetness level. The results showed that the biofertilizer treatment did not affect the growth and yield of sweet corn. However, the P. polymyxa treatment produced the tallest plants. The biofertilizer treatment did not affect yield components. It was concluded that biofertilizers did not significantly increase sweet corn growth or yield in organic farming.